Factors influencing acceptance of Ar-Rahnu: Comparison between private and state Ar-Rahnu providers in Terengganu - Abdul Rahman, Nur Najihah; Kassim, Salina (Inderscience Enterprises Ltd, 2017)
Many Muslim customers are hesitant to patronise the conventional pawnbroking shops due to the element of interest which is prohibited in Islam. Amid the demand for a shariah-compliant pawnbroking product, the first Islamic pawnbroking was setup by Maidam in Terengganu. The establishment of Ar-Rahnu provides a convenience form of credit financing which is both shariah-compliant and low cost for public to access financing. Since then, there are currently several private Ar-Rahnu providers offering Ar-Rahnu products such as Ar-Rahnu post office and Ar-Rahnu Bank Rakyat. This paper aims to review factors influencing acceptance of Ar-Rahnu between private and state Ar-Rahnu in Terengganu. This conceptual paper is primarily based on theoretical considerations, framework and models. In the first part, the paper will describe the development of the theories, and then review previous literature that provides on factors affecting customer acceptance on Ar-Rahnu. Meanwhile, the document analysis reviewed private and state Ar-Rahnu providers in Terengganu